10.1016/s1541-9800(11)70730-x (CrossRef Listing of Deleted DOIs, 2000)
Aim To map the extent, range, and characteristics of Paulo Freire's critical pedagogy in nursing education scholarship, with Pedagogy of the Oppressed as the centering text, and to examine how this scholarship moves from citation to praxis. Design Scoping review. Methods Joanna Briggs Institute scoping review methodology was followed using the Population, Concept, and Context framework. Two independent reviewers screened sources at title and abstract and full-text stages; disagreements were resolved by consensus and third-reviewer adjudication. A Depth of Use typology (Levels 0-3) was developed a priori to classify Freirean engagement from citation only to praxis with systematic evaluation. Data sources CINAHL, Scopus, Web of Science, PubMed, and ERIC were searched from January 2000 through March 2025, yielding 4240 references. Citation chaining was performed on all included sources. Results Thirty-three sources from eleven countries met eligibility criteria, spanning 2006 to 2025. Brazil (55%) and Canada (30%) produced the largest bodies of work. Empirical qualitative studies (45%) and conceptual papers (33%) predominated. 61% of sources were classified at Level 1 (framing only) and 39% at Level 2 (pedagogical design); no source met Level 3 criteria (praxis with systematic evaluation). Conscientisation was the most cited but least consistently operationalised construct. Nearly half showed no discernible decolonizing orientation. Conclusion Nursing education scholarship invokes Freirean pedagogy with growing frequency but has not proportionally advanced toward operationalisation or systematic evaluation. Within the review's typology, the absence of Level 3 sources signals an important pattern in how Freirean pedagogy is enacted and evaluated. Implications for the profession and/or patient care Nurse educators require institutional support to move beyond rhetorical alignment with Freirean pedagogy toward structured, evaluated implementation. Curricula connecting critical consciousness to collective action are essential for preparing nurses to challenge structural inequities shaping patient outcomes and health disparities. Impact This review addresses the absence of a comprehensive synthesis of how Freirean critical pedagogy is taken up in nursing education scholarship globally. No included source met the review's criteria for full enacted Freirean praxis with documented evaluative methods, indicating an important pattern between aspiration and evidence. Findings will influence nurse educators, curriculum developers, and researchers committed to social justice, anti-oppression, and decolonizing nursing education. Reporting method This scoping review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews checklist and explanation. Patient or public contribution This study did not include patient or public involvement in its design, conduct, or reporting.